ANALISIS KEBERHASILAN STRATEGI PEMASARAN DALAM UPAYA PENINGKATAN OMSET PENJUALAN UMKM - Nurjannah Nurjannah; Sri Utami (CV. KAMPUS AKADEMIK PUBLISING, 2025)
his study aims to analyze the success of marketing strategies in increasing sales turnover in micro, small, and medium enterprises (MSMEs), using a case study of Kedai Daun Teh located on Jl. Batua Raya. In the face of increasingly competitive business conditions, MSMEs are required to implement marketing strategies that are effective and adaptive to market changes. This research employs a qualitative approach with a case study method, in which data were collected through in-depth interviews, observations, and documentation involving the owner and employees of Kedai Daun Teh. The findings indicate that digital-based marketing strategies, improved service quality, and strengthened local branding implemented by Kedai Daun Teh successfully enhanced consumer appeal and had a significant impact on increasing sales turnover. The study concludes that an integrated combination of online and offline marketing strategies, along with a deep understanding of local market characteristics, is key to achieving sustainable development for MSME businesses